Energy systems contributions in 2,000 m race simulation: a comparison among rowing ergometers and water - de Campos Mello, F.; de Moraes Bertuzzi, R. C.; Grangeiro, P. M.; Franchini, E. (European Journal of Applied Physiology, 2009)
This study investigated the energy system contributions of rowers in three different conditions: rowing on an ergometer without and with the slide and rowing in the water. For this purpose, eight rowers were submitted to 2,000 m race simulations in each of the situations defined above. The fractions of the aerobic (W AER), anaerobic alactic (W PCR) and anaerobic lactic (W [La-]) systems were calculated based on the oxygen uptake, the fast component of excess post-exercise oxygen uptake and changes in net blood lactate, respectively. In the water, the metabolic work was significantly higher [(851 (82) kJ] than during both ergometer [674 (60) kJ] and ergometer with slide [663 (65) kJ] (P = 0.05). The time in the water [515 (11) s] was higher (P < 0.001) than in the ergometers with [398 (10) s] and without the slide [402 (15) s], resulting in no difference when relative energy expenditure was considered: in the water [99 (9) kJ/min], ergometer without the slide [99.6 (9) kJ/min] and ergometer with the slide [100.2 (9.6) kJ/min]. The respective contributions of the W AER, W PCR and W [La-] systems were water = 87 (2), 7 (2) and 6 (2)%, ergometer = 84 (2), 7 (2) and 9 (2)%, and ergometer with the slide = 84 (2), 7 (2) and 9 (1)%. VO 2 VO2, HR and lactate were not different among conditions. These results seem to indicate that the ergometer braking system simulates conditions of a bigger and faster boat and not a single scull. Probably, a 2,500 m test should be used to properly simulate in the water single-scull race.